Perceptions of band members towards practicing in marching band: case study VICCB / Helmi Rosli - Rosli, Helmi (2011)
The purpose of this study was to explore high school band students’ perspectives of instrumental music practice from within the motivation and attribution theory paradigm in order to elucidate the secondary student’s attitudes toward practicing. The samples for this study were the students from the Victoria Intuition Cadet Corps Band. The respondent of “is study were forty-eight band members from age 14 to 18 years old. Findings show that band members who play instrument for the extended of time are more motivated in practicing compare to those who are new in playing musical instrument. Most of band members believe that ability is an important role in order to achieve musical success.